Calculation and Study of Gamma ray Attenuation Coefficients for Different Composites - Mahdi, K.H.; Ahmed, Z.S.; Mkhaiber, A.F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this work, the total linear attenuation coefficients Âµ(cm-1) were calculated and studied for particulate reinforced polymer-based composites. Unsaturated polyester (UP) resin was used as a matrix filled with different concentrations of Al, Fe, and Pb metal powders as reinforcements. The effect of the metal powders addition at different weight percentages in the range of (10,20,30,40,50)wt % and gamma energy on attenuation coefficients was studied. The results show, as the metallic particulates content increase, the attenuation coefficients will increase too, while it, were exhibited a decrease in their values when the gamma energy increase.The total linear attenuation coefficients of gamma ray for 15 composites have been calculated using the XCOM program (version 3.1) in the energy range of 0.1-20 MeV.